PENGARUH MODEL KONSELING BEHAVIORAL DENGAN TEKNIK MODELING UNTUK MENINGKATKAN SELF AUTONOMY - Jamilah, Umi; Suarni, Ni Ketut; Gading, I Ketut (Universitas Pendidikan Ganesha, 2019)
The purpose of this reseach was to know the effect of behavioral counseling modeing technique to improve the student?s self-autonomy of class X Akomodasi Perhotelan 5 at SMK Negeri 2 Singaraja. This reseach was designed as a quasi-experimental design, which used postest-only control group design as the resach design. Population in this reseach was the student?s of class X at SMK Negeri 2 Singaraja. the sample of this reseach was taken by using purposive sampling. Self autonomy data was collected throught questionnaire method, and the data obtained was in the from of interval data. To conduct the hypothesis test it was analyzed by using non-parametric statistical analysis technique (Mann-Whitney test). The result of Mann-Whitney test showed that the significance value which obtained was 0,001. This showed that the significane value obtained can be said as significane. Therefore, it can be concluded taht ?ther was an effect of behavioral counseling modeling technique to improve the student?s self-autonomy of class X Akomodasi Perhotelan 5 at SMK Negeri 2 Singaraja? Keywords: Behavioral Counseling Model, Modeling technique, Self-Autonomy.